ABOUT NETWORKS RFWKPES16–8, RFWKPES16–4, RFWKPES16–2 AND RFWKPES16–1, CREATED ON THE BASIS NETWORK PES16–8 - Туйчієв, Гулом Нумович (Ukrainian Information Security Research Journal, 2015)
In the paper on the basis of the network PES16–8developed networks RFWKPES16–8, RFWKPES16–4,RFWKPES16–2 and RFWKPES16–1 consisting of eight,four, two, and one round function. The main advantageof the proposed network that during encryption anddecryption using the same algorithm as well as a roundfunction can be any transformation. In the networkPES16-8 length of subblock is 8, 16 and 32 bits and basison the network can create the encryption algorithm alength of subblock 128, 256 and 512 bits. In a networkPES16-8 algebraic operations are variable, as theseoperations can use the operations of addition andmultiplication modulo and XOR.